PERKIRAAN KONSUMSI ENERGI LISTRIK 2013 HINGGA 2030 ACEH TAMIANG - Rahmad Purnama; Ahmad Agus Setiawan; Suhanan Suhanan (Institut Teknologi Dirgantara Adisutjipto, 2015)
Aceh Tamiang is the province o f Aceh. The use of electrical energy is still not resolved in this case because of the lack of appropriate policies that can be taken because there is still no research how the amount of electrical energy consumption in Aceh Tamiang. the research method used is a model based approach to End Use of data population and households, the data GDP at constant prices, and consumption of electrical energy. All data is sourced from related agencies such as Bappeda Aceh Tamiang Data PLN Kuala Simpang branch. Forecasting electric energy consumption in Aceh on five sectors is the year 2013 was 48.8 GWh, while, in 2030 total energy consumption reached 76.5 GWh, this is an increase of 63.7 percent. The household sector accounted for the largest increase in consumption compared with other sectors for each year.